Rabbit hepatic arterial anatomy variations: implications on experimental design. (December 2014) - Tam, Alda L; Melancon, Marites P; Ensor, Joe; Liu, Yang; Dixon, Katherine; McWatters, Amanda; Gupta, Sanjay
Background: The VX2 rabbit model of liver cancer is commonly used to evaluate the efficacy of locoregional anticancer therapy and knowledge of the hepatic arterial anatomy in the rabbit is important for catheter-directed experiments. Purpose: To describe the normal anatomy and anatomic variations of the celiac axis and hepatic artery in the rabbit. Material and Methods: Angiograms of 222 rabbits were retrospectively reviewed. The branching pattern of the celiac axis was classified and the diameters of the major branches were measured. Paired t-tests were used to compare the difference between the average sizes of arteries. Results: Variant celiac axis or hepatic artery anatomy was noted in 25.9% of angiograms, with the gastric branches arising from the proper hepatic artery in 23.3% of cases. The celiac axis could be successfully classified into one of five distinct branching patterns in 193 (86.9%) cases. The mean diameters of the right and left hepatic arteries were 0.67 mm (95% CI [0.64, 0.7]) and 1.25 mm (95% CI [1.19, 1.31]), respectively. The mean diameters of the medial and lateral branches of the left hepatic artery were 0.63 mm (95% CI [0.6, 0.67]) and 0.91 mm (95% CI [0.86, 0.96]), respectively. The right hepatic artery was significantly smaller than the left hepatic artery and the lateral branch of the left hepatic artery (all P values <0.0001). Conclusion: Arterial variants in the rabbit are not uncommon. The proper hepatic artery often gives origin to gastric artery branches. To facilitate superselective intra-arterial intervention, the left lateral lobe of the liver should be targeted for tumor implantation because of the significant size difference between the right and left hepatic arteries.